2018
DOI: 10.3389/fimmu.2018.02387
|View full text |Cite
|
Sign up to set email alerts
|

Extended Cleavage Specificity of Human Neutrophil Elastase, Human Proteinase 3, and Their Distant Ortholog Clawed Frog PR3—Three Elastases With Similar Primary but Different Extended Specificities and Stability

Abstract: Serine proteases are major granule constituents of several of the human hematopoietic cell lineages. Four proteolytically active such proteases have been identified in human neutrophils: cathepsin G (hCG), N-elastase (hNE), proteinase 3 (hPR-3), and neutrophil serine protease 4 (hNSP-4). Here we present the extended cleavage specificity of two of the most potent and most abundant of these enzymes, hNE and hPR-3. Their extended specificities were determined by phage display and by the analysis of a panel of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 54 publications
2
48
2
Order By: Relevance
“…Proteinase K was chosen both because of its low specificity and to mimic other serine proteases that A9 and A8/A9 encounter when released from neutrophils during an inflammatory response. [56][57][58][59]69 Proteolytic decay rates were estimated by fitting a single exponential decay function to the data (Figure 3b Human A8/A9 has been described as extremely resistant to proteases; 62 however, it has not been compared to S100 proteins besides human A8 and A9. To establish a baseline expectation for S100 protein proteolytic resistance, we characterized the proteolytic resistance of a broad set of human S100s against proteinase K. As previously shown, 62 human A9 and A8 alone were rapidly proteolytically degraded, while the human A8/A9 complex exhibited strong resistance (Figure 3c, Figure 3 supplemental figures 1-2).…”
Section: A9s Evolved Proteolytic Susceptibility From a Proteolyticallmentioning
confidence: 99%
“…Proteinase K was chosen both because of its low specificity and to mimic other serine proteases that A9 and A8/A9 encounter when released from neutrophils during an inflammatory response. [56][57][58][59]69 Proteolytic decay rates were estimated by fitting a single exponential decay function to the data (Figure 3b Human A8/A9 has been described as extremely resistant to proteases; 62 however, it has not been compared to S100 proteins besides human A8 and A9. To establish a baseline expectation for S100 protein proteolytic resistance, we characterized the proteolytic resistance of a broad set of human S100s against proteinase K. As previously shown, 62 human A9 and A8 alone were rapidly proteolytically degraded, while the human A8/A9 complex exhibited strong resistance (Figure 3c, Figure 3 supplemental figures 1-2).…”
Section: A9s Evolved Proteolytic Susceptibility From a Proteolyticallmentioning
confidence: 99%
“…In order to perform all the different functions needed at the area of inflammation, the proteases stored and secreted by the neutrophils have relatively broad specificities both concerning their primary and extended specificities. We have recently performed detailed studies of the extended specificities of three out the four active serine proteases stored in granules of human neutrophils, hCG, hNE and hPR-3 [9,15]. Phage display analysis and validation by a large panel of recombinant protein substrates have shown that hCG is a dual chymase and tryptase with a dominating chymase activity against aromatic amino acids, and with a tryptic activity primarily against lysine that is only 2-3 times lower than the major chymotryptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The three neutrophil proteases used for this study were commercial preparations, where the original source of the protein was blood neutrophils (Figure 1). The same batches for all three of these enzymes have been analyzed for purity by SDS PAGE analysis and for activity on chromogenic substrate assay, phage display and a panel of recombinant substrates in a previously published study [15] ( Figure 1). In this study we show that the enzymes are pure and that hPR3 and hNE both are elastases whereas hCG is a dual enzyme with both chymase and tryptase activity, the tryptase specificity with strong preference for Lys over Arg [9,15].…”
Section: The Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As neither chromogenic substrates nor phage display resulted in any information concerning the extended specificities of these three platypus enzymes, we instead tried a third alternative; to use a new type of recombinant substrate. A panel of such substrates has previously been designed and produced for the verification of the extended cleavage specificity following phage display analysis for a number of previously analysed mammalian hematopoietic and coagulation serine proteases [17,[21][22][23][24][25][26][27][28][29][30].…”
Section: Analysis Of the Extended Cleavage Specificity By The Use Of mentioning
confidence: 99%